2016
DOI: 10.1108/itp-06-2014-0123
|View full text |Cite
|
Sign up to set email alerts
|

Towards a better understanding of system analysts’ tacit knowledge

Abstract: Purpose – The purpose of this paper is to elicit tacit knowledge exhibited in expert information system (IS) professionals in a form that can be shared with others; and to develop categorical framework suggesting key content areas of tacit knowledge in the requirements analysis domain. Design/methodology/approach – Requirements analysis is selected as the main focus of this study due to the importance of this phase to the success of IS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 82 publications
0
12
0
3
Order By: Relevance
“…The experience gained by each teacher certainly varies based on situations and conditions that cannot be predicted. Tacit knowledge is not easily articulated and converted to explicit knowledge (Mohajan, 2016;Prasarnphanich et al, 2016;Addis, 2016;Cairo Battistutti, 2017;Zang et al, 2015;Spraggon & Bodolica, 2017). Nevertheless, tacit knowledge can be empowered by SECI Model (Li, Liu & Zhou, 2018;Nonaka & Hirose, 2018;Chatterjee et al, 2018;Sasaki, 2017;Lievre & Tang, 2015;Stanica & Peyd-…”
mentioning
confidence: 99%
“…The experience gained by each teacher certainly varies based on situations and conditions that cannot be predicted. Tacit knowledge is not easily articulated and converted to explicit knowledge (Mohajan, 2016;Prasarnphanich et al, 2016;Addis, 2016;Cairo Battistutti, 2017;Zang et al, 2015;Spraggon & Bodolica, 2017). Nevertheless, tacit knowledge can be empowered by SECI Model (Li, Liu & Zhou, 2018;Nonaka & Hirose, 2018;Chatterjee et al, 2018;Sasaki, 2017;Lievre & Tang, 2015;Stanica & Peyd-…”
mentioning
confidence: 99%
“…Employees require particular practical skills ("know-how") to perform tasks efficiently (Tsohou et al, 2012). These can be learned and developed through independent learning or detecting and emulating the skills of others, which are the approaches of a tacit KS environment (Letmathe et al, 2012;Prasarnphanich et al, 2016). This study found all three case studies provided minimal basic training to new employees.…”
Section: Information and Communication Technology Know-how And Trainingmentioning
confidence: 92%
“…The tacit dimension of IT innovations (Birkinshaw et al, 2002) is derived not only from internal firm-specific learning processes (Cohen and Levinthal, 1990) but also from the inherent characteristics of the IT product or service. Complexity of the IT innovation and tacitness of the knowledge transferred to the customers are then considered here as key factors of the process of KT initiated by the IT supplier (Prasarnphanich et al, 2016).…”
Section: Complexity and Tacitnessmentioning
confidence: 99%